2013
DOI: 10.1007/s11010-013-1851-z
|View full text |Cite
|
Sign up to set email alerts
|

Foxc2 over-expression in bone marrow mesenchymal stem cells stimulates osteogenic differentiation and inhibits adipogenic differentiation

Abstract: The forkhead box C2 (Foxc2) protein, a member of the forkhead/winged helix transcription factor family, is strongly expressed in developing embryo and is required in various developmental processes. However, the precise function of Foxc2 in osteoblast differentiation remains largely unknown. The present study investigated the role of Foxc2 overexpression on osteogenic and adipogenic differentiations. In our experiment, rabbit bone marrow mesenchymal stem cells (BMSCs) were transduced with lentiviral vectors co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 39 publications
3
22
0
Order By: Relevance
“…In fact, several studies have described the essential roles of FOXC2 in skeletal development and osteogenesis, including the capability to enhance osteogenic differentiation in various cells and indispensable roles in neurocranium and vertebrae development [ 42 – 45 ]. Interestingly, FOXC2 has also been reported to inhibit adipogenic differentiation and was associated with bone mineral density in community-dwelling Japanese individuals [ 46 48 ]. As the reciprocal relationship between osteogenesis and adipogenesis during mesodermal differentiation has been most clearly elucidated, our observation together with previous studies indicates a potential key role of FOXC2 in early osteoblastic phenotype commitment and bone metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, several studies have described the essential roles of FOXC2 in skeletal development and osteogenesis, including the capability to enhance osteogenic differentiation in various cells and indispensable roles in neurocranium and vertebrae development [ 42 – 45 ]. Interestingly, FOXC2 has also been reported to inhibit adipogenic differentiation and was associated with bone mineral density in community-dwelling Japanese individuals [ 46 48 ]. As the reciprocal relationship between osteogenesis and adipogenesis during mesodermal differentiation has been most clearly elucidated, our observation together with previous studies indicates a potential key role of FOXC2 in early osteoblastic phenotype commitment and bone metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Adult stem cells are tissue-specific cells that retain the ability to differentiate into a variety of cell lineages and have self-renewal capabilities (Xia and Cao, 2013;You et al, 2013). Mesenchymal stem cells (MSCs) are one class of adult stem cells that have generated a significant amount of interest as a potential therapy for lung disease (Mei et al, 2007;Mei et al, 2010;Lee et al, 2011;Barisione et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies found Foxc2 enhanced mice pre-adipocytes proliferation and inhibited apoptosis via activating Akt/mTORC1 signaling pathway23. Foxc2 stimulates osteogenic differentiation and inhibits adipogenic differentiation in bone marrow mesenchymal stem cells, and in white adipocytes2425. Overexpression of Foxc2 in adipocytes prevents diet-induced obesity and insulin resistance2627.…”
mentioning
confidence: 98%